2003
DOI: 10.1167/iovs.03-0490
|View full text |Cite
|
Sign up to set email alerts
|

The Toxic and Stress Responses of Cultured Human Retinal Pigment Epithelium (ARPE19) and Human Glial Cells (SVG) in the Presence of Triamcinolone

Abstract: TA was cytotoxic to both SVG and ARPE19 cells, with higher efficacy on SVG. TA caused the activation of the caspase-3 pathway more readily than the cell-protective c-fos and c-jun pathways in SVG cells, making those cells more vulnerable than the ARPE19 cells. The results suggest that TA toxicity in one cell type may not reliably indicate its toxicity in other cells. Different cells within the retina may react to TA differently, or TA may cause changes in the gene expressions differentially with different conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 26 publications
1
66
0
3
Order By: Relevance
“…We therefore speculate that, in the present study, the intraocular use of TA decreased postoperative inflammation, and inhibited subsequent fibrous tissue formation and the recurrence of RD to some extent. This possibility is supported by clinical observations (13,16,25), and by the finding that TA inhibits RPE and retinal glial cell proliferation in vitro (26). Corticosteroids are known to elevate IOP in susceptible patients, much like the elevation of IOP observed in some eyes following TA injection (27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 81%
“…We therefore speculate that, in the present study, the intraocular use of TA decreased postoperative inflammation, and inhibited subsequent fibrous tissue formation and the recurrence of RD to some extent. This possibility is supported by clinical observations (13,16,25), and by the finding that TA inhibits RPE and retinal glial cell proliferation in vitro (26). Corticosteroids are known to elevate IOP in susceptible patients, much like the elevation of IOP observed in some eyes following TA injection (27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 81%
“…Our recent in vitro studies showed that triamcinolone could exert a cytotoxic effect on retinal pigment epithelial cells and glial cells. 20,21 In addition to localizing in the vitreous cavity, triamcinolone has been detected in the aqueous humor after intravitreal injections. 22 The presence of triamcinolone acetonide in the anterior chamber may affect the health of the corneal endothelium, which plays an important role in the function of the cornea.…”
Section: Introductionmentioning
confidence: 99%
“…Similar improvement in drugdelivery efficiency in response to polymeric nanoparticles has also been reported by previous researchers. 42 The most common injection doses of triamcinolone acetonide used in ophthalmic practice are 4-20 mg. 10 Because the vitreous volume in humans is about 4 mL, 32 the equivalent vitreous concentration of this corticosteroid thus corresponds to 1-5 mg/mL. Although the experimental TAA concentration in the present TAA/DA-Chit nanoparticles (0.1 mg/mL) was much less than the clinical concentration of triamcinolone acetonide, downregulation of VEGF mRNA expression was significant.…”
Section: Vegf Mrna Expression Efficiencymentioning
confidence: 79%
“…13,14 For example, triamcinolone acetonide is toxic to human retinal pigment epithelial cells in concentrations from 0.01 mg/mL to 1 mg/mL, resulting in apoptosis. 31,32 The cytotoxicity of TAA/DA-Chit nanoparticles was thus evaluated using the CCK-8 assay. 26 After human retinal pigment epithelial cells had been incubated with TAA at 0.1 mg/mL for 1-5 days, cell viability decreased from 78.3% to 40.4% (Figure 6), suggesting strong cytotoxicity.…”
Section: Cytotoxicity Of Taa/da-chit Nanoparticlesmentioning
confidence: 99%